Cardiopulmonary Bypass Strategy to Facilitate Transfusion-Free Congenital Heart Surgery in Neonates and Infants - Boettcher, Wolfgang; Dehmel, Frank; Redlin, Mathias; Sinzobahamvya, Nicodème; Photiadis, Joachim (The Thoracic and Cardiovascular Surgeon, 2020)
Priming the cardiopulmonary bypass (CPB) circuit without the addition of homologous blood constitutes the basis of blood-saving strategies in open-heart surgery. For low-weight patients, in particular neonates and infants, this implies avoidance of excessive hemodilution during extracorporeal circulation. The circuit has to be miniaturized and tubing must be cut as short as possible to reduce the priming volume to prevent unacceptable hemodilution with initiating CPB. During perfusion, measures should be taken to prevent blood loss from the primary circuit to avoid replacement by additional volume. Favorable factors such as mild hypothermia/normothermia and high heparin concentrations during extracorporeal circulation promote earlier hemostasis after coming off bypass.Lower mortality score, first chest entry, higher hemoglobin concentration before going on bypass, and shorter CPB duration support transfusion-free CPB procedure. Reduced postoperative morbidity and mortality were observed when CPB was performed without blood transfusion. In our experience, this can be achieved in at least 70% of CPBs, even in low-weight patients.Bloodless CPB circuit priming should become a widespread reality, even in neonates and young infants, in any open-heart procedure.
Keywords: cardiopulmonary bypass; CPB; blood transfusion; neonate; infant; congenital heart disease; CHD